0170 Should simulation based medical training be integrated into final year medical student curriculum in order to better prepare for foundation training?. (2nd November 2015) - Hutchinson, Kate L; Abayalingam, Mayavan; Butcher, Charles; Eneje, Odiri; Mitchell, Andrew; Lane, Rebecca; Smith, Robert; Carby, Martin
Abstract : Background: Foundation Training Programme acts as a bridge from medical school to specialist training. The Royal College of Physicians refers to Foundation Training (FT) as "practical experience needed to work independently", 1 however many students feel under-prepared for this daunting step. High fidelity simulation may be a valuable tool in bridging this gap through exposure to clinical scenarios in a controlled environment. Methodology: 15 final year medical students participated in 2-week Simulation Training (ST) in which candidates portrayed the role of Foundation Doctor. Scenarios covered clinical pathologies including heart failure and pneumonia followed by a formal debrief. Data from focus groups and feedback forms before and after ST were analysed to determine candidate's concerns about FT and benefit of ST in addressing these. Results: Pre-simulation; All students did not feel prepared for FT, particularly highlighted was a lack of practical exposure in making clinical decisions. Post-simulation, All felt empowered to make clinical decisions through learning from practical experience with ST forming a link between theory and real life. All of the students felt ST would be useful in medical school training. Conclusions and recommendations: This small study found ST to be an effective tool in helping medical students ease into FT. Reference: https://www.rcplondon.ac.uk/medical-careers/foundation-doctors